KREATIVITAS DAN PENGETAHUAN SISWA PADA MATERI ASAM-BASA MELALUI PENERAPAN PROJECT BASED LEARNING DENGAN PRODUK KREATIF TERI PUTER - Nailissatin Khumaeroh; Woro Sumarni (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
STUDENTS’ CREATIVITY AND KNOWLEDGE ON ACID-BASE TOPIC THROUGH THE APPLICATION OF PROJECT-BASED LEARNING WITH TERI PUTER CREATIVE PRODUCTS AbstractCreativity is one of the most needed competencies in the 21st century. This study aims to analyze students' creativity and knowledge on acid-base material through the application of Project Based Learning with Teri Puter Creative Products. The study was conducted at SMA Negeri 1 Bae Kudus with 35 research subjects in class XI MIPA 6 in the 2018/2019 school year. Data collection techniques using test and non-test instruments that have been declared valid and reliable. The results showed as many as 74% of students were in creative criteria and were very creative with the highest percentage in the originality indicator and the lowest percentage in the fluency indicator, while for the ability of knowledge by 40% who had good criteria and very good. The highest achievement is on the indicator to calculate the pH of acid-base solution and the lowest achievement on the indicator to calculate the concentration of [H+] and [OH-] in the solution. Positive responses are given by students with project based learning that has been applied. AbstrakKreativitas merupakan salah satu kompetensi yang amat dibutuhkan pada abad ke-21. Penelitian ini bertujuan untuk menganalisis kreativitas dan pengetahuan siswa pada materi asam-basa melalui penerapan Project Based Learning dengan Produk Kreatif Teri Puter. Penelitian dilaksanakan di SMA Negeri 1 Bae Kudus dengan subjek penelitian sebanyak 35 siswa kelas XI MIPA 6 pada tahun ajaran 2018/2019. Teknik pengumpulan data menggunakan instrumen tes dan non tes yang telah dinyatakan valid dan reliabel. Hasil penelitian menunjukkan sebanyak 74% siswa berada pada kriteria kreatif dan sangat kreatif dengan persentase tertinggi pada indikator originality dan persentase terendah pada indikator fluency, sedangkan untuk kemampuan pengetahuan sebesar 40 % yang berkriteria baik dn sangat baik. Pencapaian tertinggi yaitu pada indicator menghitung pH larutan asam-basa dan pencapaian terendah pada indicator menghitung konsentrasi [H+] dan [OH-] dalam larutan. Tanggapan positif diberikan oleh siswa dengan project based learning yang telah diterapkan.